2019
DOI: 10.1155/2019/7135974
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Derived Stem Cells Promote Seawater-Immersed Wound Healing by Activating Skin Stem Cells via the EGFR/MEK/ERK Pathway

Abstract: Seawater (SW) immersion can increase the damage of skin wounds and produce refractory wounds. However, few studies have been conducted to investigate the mechanisms of SW immersion on skin wounds. In our current study, we investigated the effect of human adipose-derived stem cells (hADSCs) on the repair of SW-treated full-thickness skin wounds and the underlying mechanisms. The results showed that SW immersion could reduce the expression of EGF and suppress the activation of the MEK/ERK signaling pathway. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The results showed that the protein expression level of EGF was significantly higher in the control and the SW+ADSC groups than in the SW group or the SW+DMEM group ( Figure 8(b) ). Microscopic observations of wound sections showed that the skin in the SW and the SW+DMEM groups was significantly thinner than that in the control and SW+ADSC groups ( Figure 8(c) ) [ 165 ]. During wound healing, a reduction in wound inflammation is associated with a switch in macrophage polarization from a proinflammatory (M1) to a prorepair (M2) phenotype [ 166 ].…”
Section: Regenerative Medicine Based On Adscsmentioning
confidence: 99%
“…The results showed that the protein expression level of EGF was significantly higher in the control and the SW+ADSC groups than in the SW group or the SW+DMEM group ( Figure 8(b) ). Microscopic observations of wound sections showed that the skin in the SW and the SW+DMEM groups was significantly thinner than that in the control and SW+ADSC groups ( Figure 8(c) ) [ 165 ]. During wound healing, a reduction in wound inflammation is associated with a switch in macrophage polarization from a proinflammatory (M1) to a prorepair (M2) phenotype [ 166 ].…”
Section: Regenerative Medicine Based On Adscsmentioning
confidence: 99%
“…Our previous study confirmed that seawater immersion significantly delays wound healing, and that human ADSCs (hADSCs) can differentiate into skin stem cells and increase the proliferation and migration of autologous skin stem cells to promote the repair of seawater immersion wounds [ 9 ]. However, the effect and mechanism of vascularization have not yet been explored.…”
Section: Introductionmentioning
confidence: 75%
“…The wounds continue to aggravate, and can eventually lead to mortality. In our previous study [ 9 ], a model of seawater immersion wounds was established, and it was observed that the healing efficiency of seawater immersion wounds compared with that of normal skin wounds was significantly delayed and produced refractory wounds. At the same time, hADSCs significantly accelerated the healing of seawater-immersed skin wounds by promoting skin stem cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…The optical density (OD) was measured at 450 nm with a microplate reader (Tecan, Thermo Scientific, United States). For EdU assays, the experiments were performed according to the manufacturer’s instructions ( Xiong et al, 2019 ). Then, the cells were observed under a fluorescence microscope (Zeiss HLA100, Shanghai, China) and analyzed by using ImageJ software (Bethesda, MD, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated from tissues or cells using Trizol ® Reagent (Life Technologies, United States) and reverse transcribed into cDNA using a cDNA synthesis kit (Thermo Scientific) according to the manufacturer’s instructions. qRT-PCR was performed as previously reported ( Xiong et al, 2019 ). Melt curves were established for the reactions, and the normalized fold expression was calculated using the 2 −ΔΔ Ct method.…”
Section: Methodsmentioning
confidence: 99%